Design and evaluation of quantitative MRI phantoms to mimic the simultaneous presence of fat, iron, and fibrosis in the liver. Issue 2 (12th August 2020) - Zhao, Ruiyang; Hamilton, Gavin; Brittain, Jean H.; Reeder, Scott B.; Hernando, Diego
Abstract : Purpose: To design, construct, and evaluate quantitative MR phantoms that mimic MRI signals from the liver with simultaneous control of three parameters: proton‐density fat fraction (PDFF), R 2 ∗, and T1 . These parameters are established biomarkers of hepatic steatosis, iron overload, and fibrosis/inflammation, respectively, which can occur simultaneously in the liver. Methods: Phantoms including multiple vials were constructed. Peanut oil was used to modulate PDFF, MnCl2 and iron microspheres were used to modulate R 2 ∗, and NiCl2 was used to modulate the T1 of water (T1, water ). Phantoms were evaluated at both 1.5 T and 3 T using stimulated‐echo acquisition‐mode MRS and chemical shift–encoded MRI. Stimulated‐echo acquisition‐mode MRS data were processed to estimate T1, water, T1, fat, R 2, water ∗, and R 2, fat ∗ for each vial. Chemical shift–encoded MRI data were processed to generate PDFF and R 2 ∗ maps, and measurements were obtained in each vial. Measurements were evaluated using linear regression and Bland‐Altman analysis. Results: High‐quality PDFF and R 2 ∗ maps were obtained with homogeneous values throughout each vial. High correlation was observed between imaging PDFF with target PDFF (slope = 0.94‐0.97, R 2 = 0.994‐0.997) and imaging R 2 ∗ with target R 2 ∗ (slope = 0.84‐0.88, R 2 = 0.935‐0.943) at both 1.5 T and 3 T. The values of R 2, fat ∗ and R 2, water ∗ were highly correlated with slope close to 1.0 at both 1.5 T (slope = 0.90, R 2 = 0.988) and 3 T (slope = 0.99, R 2 = 0.959), similar to the behavior observed in vivo. The value of T1, water (500‐1200 ms) was controlled with varying NiCl2 concentration, while T1, fat (300 ms) was independent of NiCl2 concentration. Conclusion: Novel quantitative MRI phantoms that mimic the simultaneous presence of fat, iron, and fibrosis in the liver were successfully developed and validated.